Penglibatan protein fosfotirosin dalam infeksi plasmodium berghei - Hasidah Mohd Sidek; Chee , Suan Kim; Rohani Abd. Kadir (Universiti Kebangsaan Malaysia, 2000)
The process of phosphorylation-dephosphorylation including those mediated by tyrosine kinase signaling pathway has been reported to influence the process of host invasion by malarial parasite. This study was carried out to assess the relationship between Plasmodium berghei infection and the erythrocyte level of phosphotyrosine-containing proteins in mice. Coomassie blue staining of SDS-PAGE gel indicated the presence of several erythrocyte protein bands between 14.4kDa and 97.4kDa in size in the experimental mice. Western blotting [primary antibody = anti-phosphotyrosine; secondary antibody = anti-IgG mouse conjugate with HRP] failed to show the presence of phosphotyrosine-immunoreactive proteins. Dot blotting however showed the presence of immunoreactive proteins in mice infected with Plasmodium berghei. The immunoreactive proteins were absent in non-infected mice. Densitometric analysis of these immunoreactive proteins indicated that the relative level of phosphotyrosine-containing proteins increased with infection reaching a maximum on day 12 post-infection parallel to a maximum in the level of parasitemia. Data from this study suggests the involvement of tyrosine phosphorylation in Plasmodium berghei infection.